Pengembangan Model Keberlanjutan e-filing di Palembang Menggunakan Partial Least Square Structural Equation Models (PLS-SEM) - Saluza, Imelda; Sartika, Dewi (Universitas Diponegoro, 2019)
DGT (Directorate General of Taxation) continues to optimize the collection of annual tax returns by facilitating technology-based tax service systems, one of which is e-filing that has been running since 2016. However, e-filing turned out to have less influence on the delivery of annual tax returns as reflected in the electronic annual tax returns monitoring data that only met 78% of the 2017 target. This is caused by various problems that arise during the use of e-filing such as individual technology capabilities, loss of efin, forgetting DGT Online account passwords to lack of awareness about the importance of submitting annual tax returns. Problems encounter during the use of e-filing are the basis for evaluating the continued use of e-filing in Palembang. The development of a conceptual model was conducted to evaluate the sustainability of the use of e-filing. The development of a conceptual model basically has a scarcity of supporting theories used and has a complex model. To overcome this problem, Partial Least Squares (PLS) Structural Equation Model (SEM) could be applied to. The results of data analysis found that information quality and service quality did not have a positive influence on the sustainability of the use of e-filing and the level of correlation between information quality, system quality, service quality, and individual ability was still small towards the sustainability of the use of e-filing. It could be concluded that the quality of information and service provided by DGT has the opposite effect that does not even influance the sustainability of e-filing usage. However, the quality of the system and the ability of individuals to give effect to e-filing usage in reporting in reporting annual tax returns. Therefore, DGT is expected to improve the quality of the system of e-filing expecially in the function of e-filing, ease of use, usefullness of e-filing in reporting annual tax return. In additory it is necessary to carry out socialization and training on e-filing to improve the ability of individuals to report online their annual tax report. The findings of this research are very important for the Tax office in Palembang to analyze the sustainability of the use of e-filing that has been proven empirically, multidimensional and in a specific context. The result of the study could be used as a reference to improve overall quality of taxation for the sake of sustainable use of e-filing.Â